Pengaruh Harga, Kualitas Produk, Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Usaha Rumahan Kerupuk Kelempang Cek Isyah Palembang - Agil Alparabi; Hilda Hilda; Chici Rima Putri Pratama (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of this research is to determine the influence of price, product quality and service quality on customer satisfaction at the home business Kerupuk Kelempang Cek Isyah Palembang. This research uses primary data with a quantitative approach. Classic assumption testing techniques and hypothesis testing using IBM SPSS 26 statistical analysis. The results of this research show that Price has a positive and significant effect on Customer Satisfaction, Product Quality has a positive and significant effect on Customer Satisfaction, and Service Quality has a positive and significant effect on Customer Satisfaction . Price, product quality and service quality simultaneously have a positive and significant effect on customer satisfaction.